ANALISIS STRATEGI PENGEMBANGAN BISNIS “HAPPY HONEY BEE” ENGLISH LEARNING CENTRE AND COURSE MENGGUNAKAN SWOT ANALYSIS - Rahmawati Riantisari; Arifin Arifin; Kurni Astiani (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
This study aimed to analyze the position of “Happy Honey Bee” English Learning Centre and Course in its business environment. This study used qualitative research method. The data was collected using observations and interviews. The respondent of interview was owner and manager of the company. The data was analyzed using SWOT analysis that developed by Pearce and Robinson (2008). We used IFAS (Internal Factor Analysis Summary) matrix analysis, EFAS (External Factor Analysis Summary), and SWOT (Strengths Weaknesses Opportunities Threats) matrix analysis. The results showed that the condition of “Happy Honey Bee” is not profitable enough. The calculation of EFAS is 0.246 and IFAS is -0.523. In the SWOT matrix diagram, the company was in quadrant 3. The quadrant indicated that the company faces many obstacles, but it still has enough time and sufficient resources to find solutions.